The significant relationship between macroeconomic variables and gold price / Nurul 'Afifah Omar - Omar, Nurul 'Afifah (Faculty of Business and Management, 2014)
All praises to the Allah Almighty the most merciful and the most benevolent for giving me an opportunity and show me the right way. Syukur, Alhamdulillah my highest gratitude to Allah S.W.T. for providing me strength to complete this research paper. I am sincerely to thank the entire people surround me who had helped me in order for me to complete this research paper. To the entire lecturer in the UiTM Segamat, Johor especially my supervisor, Madam Siti Salwa binti Hassan, who had guided me and teach me in preparing this report. Her comment on my research paper had assisted me to improve the content in this research paper. I could not repay her ideas and comment in conducting this research paper. Besides, I also want to give a warmest thankful to my second examiner Encik Syamsul Samsudin who also had given an assistance for preparing this research paper. Not to forget, all my friends who had been together through thick and thin in order to prepare this research paper. I will not forget the kindness and the sharing of information with each other to complete this research paper. Then, I want to express my appreciation to my family members who had given support to me to complete this research paper. Thank you